Fifth Lumbar Vertebral Shape in Early-Stage Lumbar Spondylolysis: Three-Dimensional Bone Morphology Analysis Using Homologous Models - Yuji Yamane; Hajime Toda; Masaki Katayose (Spine Surgery and Related Research)
Introduction: Fifth lumbar (L5) vertebral morphology contributes to spondylolysis. However, there are no comprehensive examinations of the three-dimensional vertebral shape in early-stage cases. This study aimed to investigate the overall L5 vertebral shape in early-stage spondylolysis. Methods: Homologous models of the L5 vertebra were constructed using computed tomography data from 72 patients with early-stage spondylolysis (SP group) and 95 patients without spondylolysis (CON group). Principal component analysis was performed on the three-dimensional coordinates of all vertices of the generated homologous models. The groups' principal component scores were compared. Results: Principal component (PC) 3, which represents the morphology of the cross-sectional area of the vertebral body; length of pedicle, neural arch, and isthmus; shape of the vertebral body; and spinous process orientation were significantly higher in the SP group than in the CON group. Additionally, the SP group showed higher values for PC10, which represents the morphology of the anteroposterior length of the vertebral body and transverse process orientation. Compared to the CON group, the SP group's PC3 had a smaller cross-sectional vertebral body area, longer pedicle and neural arch length, larger dorsal wedge shape of the vertebral body, horizontally oriented spinous process, and a shorter isthmus length. PC10, compared with the CON group, indicated the SP group had a shorter anteroposterior length of the superior and inferior surfaces of the vertebral body and a coronally oriented transverse process. Conclusions: The overall L5 vertebral shape differed between individuals with and without early-stage spondylolysis. Our findings suggest that a wedge-shaped vertebral body and shorter isthmus length may be associated with spondylolysis development. Our study may be valuable in elucidating spondylolysis pathogenesis and may contribute to early detection and prevention.